Foundations of Java for ABAP Programmers - Rooneyo, Alistair (Apress, 2012)
Java has been a part of developers’ vocabularies since 1995. At first it was thought of as being a nice, neat little language that could do some amazing things for the Internet. However, the language soon matured, and it still kept its simple approach. Developers started to realize the awesome power of a clean uncluttered alternative to C/C++. It wasn’t long before visionaries in the industry discovered that Java could be further extended into an “enterprise” language. Thus J2EE (Java 2 Enterprise Edition) was born. This has also matured into a solid base for running three-tier, web-based, enterprise systems. If anyone doubts the industrial strength of these systems, there are now a wealth of bluechip corporations using J2EE. They use IBM WebSphere and other enterprise systems to create very large, robust, and “externalized” systems. The dot-com boom may have adjusted itself somewhat, but it is by no means gone. The statement that the Gartner group made a few years ago, that corporations would have to externalize their data or lose out to competitors that have, is still very valid. Can you imagine working with a bank that did not offer online banking? They wouldn’t survive for very long if their competitors were all “webified”! So, in 2001, one of the most innovative ERP companies, SAP, saw an opportunity to bring Java into its development environment. SAP has said that Java and ABAP will coexist as development languages. With Web Application Server (WAS) 6.40, we have seen this become a reality. Although there is still room for improvement (isn’t there always?) we now have a credible SAP platform for delivering web services.